2022
DOI: 10.3389/fphar.2022.970234
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of ion channels to shaping macrophage behaviour

Abstract: The expanding roles of macrophages in physiological and pathophysiological mechanisms now include normal tissue homeostasis, tissue repair and regeneration, including neuronal tissue; initiation, progression, and resolution of the inflammatory response and a diverse array of anti-microbial activities. Two hallmarks of macrophage activity which appear to be fundamental to their diverse cellular functionalities are cellular plasticity and phenotypic heterogeneity. Macrophage plasticity allows these cells to take… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 301 publications
(342 reference statements)
0
10
0
Order By: Relevance
“…Interestingly, Cluster 1 involved predominantly potassium and voltage gated channels pathway. Potassium channels and other voltage gated channels have recently been shown to have important roles in macrophage function such as iNOS production, phagocytosis and intracellular signalling [ 67 ]. Transcriptional activity (DoroThea) promoting tumourigenesis and regulation of inflammation was also different between the three clusters of macrophages suggesting that they could influence tumour growth and tumoural inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Cluster 1 involved predominantly potassium and voltage gated channels pathway. Potassium channels and other voltage gated channels have recently been shown to have important roles in macrophage function such as iNOS production, phagocytosis and intracellular signalling [ 67 ]. Transcriptional activity (DoroThea) promoting tumourigenesis and regulation of inflammation was also different between the three clusters of macrophages suggesting that they could influence tumour growth and tumoural inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with previous studies reporting the expression and activity of several members of the TRP family (including TRPM2/4/7/8, TRPC1/3/6 [canonical], TRPV1/2/4, TRPA1 [ankyrin], TRPM1/2/3 [mucolipins], TRPP2) in myeloid cells. These channels have been implicated in the control of cell proliferation and survival, polarisation, mobility, phagocytosis, intercellular communication, and inflammatory responses (as reviewed in (Santoni, Morelli et al 2018, Selezneva, Gibb et al 2022)).…”
Section: Discussionmentioning
confidence: 99%
“…Ion channels are transmembrane proteins that enable the passage of ions across cell membranes and regulate physiological processes (15)(16)(17)(18)(19)(20)(21)(22)(23). Recent studies have shown ion channels regulate macrophage function (3,4). Several ion channels in macrophages are implicated in immune responses and inflammatory diseases.…”
Section: Ion Channels In Macrophagesmentioning
confidence: 99%
“…Several ion channels in macrophages are implicated in immune responses and inflammatory diseases. The macrophage ion channels include potassium channel, transient receptor potential (TRP) channel, calcium channel, mechanosensitive Piezo channel, chloride channel, and proton channel (3)(4)(5).…”
Section: Ion Channels In Macrophagesmentioning
confidence: 99%
See 1 more Smart Citation